Coupled transcription and processing of mouse ribosomal RNA in a cell-free system. - Mishima, Y (1985)
An in vitro processing system of mouse rRNA was achieved using an RNA polymerase I-specific transcription system, (S100) and recombinant plasmids consisting of mouse rRNA gene (rDNA) segments containing the transcription initiation and 5'-terminal region of 18S (or 41S) rRNA. Pulse-chase experiments showed that a specific processing occurred with transcripts of the plasmid DNAs when the direction of transcription was the correct orientation relative to the 18S rRNA coding sequence, but not with transcripts of the DNA templates in which this coding sequence was in the opposite orientation. From the S1 nuclease protection analyses, we concluded that there are several steps of endonucleolytic cleavage including one 105 nucleotides upstream from the 5' end of 18S rRNA. Intermediates cleaved at this site were identified in in vivo processing of rRNA. This result indicates that endonucleolytic cleavage takes place 105 nucleotides upstream from the 5' terminus of 18S rRNA prior to the formation of mature 18S rRNA. Trimming or cleavage of the 105 nucleotides may be involved in the formation of the 5' terminus of mature 18S rRNA.